Behaviour of Listeria monocytogenes LMG 10470 in Poultry Meat and its Control by the Bacteriocin Plantaricin UG 1 - Enan, Gamal (International Journal of Poultry Science, 2006)
Growth of the Listeria monocytogenes LMG10470 (L. monocytogenes) pathogen were prevented by partially purified plantaricin UG1 within almost 2-3 days in uncooked and cooked poultry meat and dry mortadella samples of chicken and turkey. Inoculation of the experimental samples of cooked and uncooked meat and dry mortadella of chicken and turkey by the Lactobacillus plantarum UG1 Lact. plantarum UG1) cells producing the bacteriocin plantaricin UG1 resulted in inactivation of the all experimental L. monocytogenes cells within almost 3-4 days. By further storage of the treated samples, a slight resurgence of L. monocytogenes growth was observed in almost all poultry samples treated with plantaricin UG1, but was not observed in all poultry samples of cooked and uncooked meat and mortadella samples of chicken and turkey inoculated with the Lact. plantarum UG1 cells producing plantaricin UG1